2019
DOI: 10.1111/1475-6773.13241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of travel distance and rurality of residence on initial surveillance for hepatocellular carcinoma in VA primary care patient with cirrhosis

Abstract: Objective To determine the relationship between travel distance and surveillance for hepatocellular carcinoma among veterans with cirrhosis. Data Sources Veterans Health Administration (VHA) inpatient and outpatient administrative data were linked to geocoded enrollee files. CMS‐VHA merged data were used to assess receipt of Medicare‐financed non‐VA imaging. Study Design A retrospective cohort of US veterans diagnosed with cirrhosis between 2009 and 2015 was examined. First available abdominal imaging followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…For example, Rongey et al evaluated 156,965 US veterans with chronic HCV to determine the impact of rural residency on quality of liver care and observed that patients in rural regions were significantly less likely to access HCV specialty care 11 . Similar studies using the Veterans Affairs database also observed that rural residency was associated with lower rates of receiving HCC surveillance 32 . Ross et al evaluated data from the Scientific Registry of Transplant Recipients from 2002 through 2014 and observed that patients from low‐income households or from rural geographic regions had significantly greater liver transplantation waitlist mortality, primarily driven by disparities in resources on low‐income and rural regions 33 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, Rongey et al evaluated 156,965 US veterans with chronic HCV to determine the impact of rural residency on quality of liver care and observed that patients in rural regions were significantly less likely to access HCV specialty care 11 . Similar studies using the Veterans Affairs database also observed that rural residency was associated with lower rates of receiving HCC surveillance 32 . Ross et al evaluated data from the Scientific Registry of Transplant Recipients from 2002 through 2014 and observed that patients from low‐income households or from rural geographic regions had significantly greater liver transplantation waitlist mortality, primarily driven by disparities in resources on low‐income and rural regions 33 .…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the complexity of care involved in HCC, such as diagnosis, surveillance, and other treatments not included in our analysis. For instance, several reports have shown rural residents were found to have lower rates of antiviral treatment for hepatitis, decreased rates of surveillance, and higher stages of disease at diagnosis 19–21 . Therefore, the disparities noted in the current study of patients with early‐stage HCC are likely multifactorial and partially contributed to increased distance from specialty care.…”
Section: Discussionmentioning
confidence: 74%
“…For instance, several reports have shown rural residents were found to have lower rates of antiviral treatment for hepatitis, decreased rates of surveillance, and higher stages of disease at diagnosis. [19][20][21] Therefore, the disparities noted in the current study of patients with early-stage HCC are likely multifactorial and partially contributed to increased distance from specialty care. Furthermore, additional complexity is added when one considers that while distance from treatment centers is often measured in miles, this often understates travel difficulty.…”
Section: Discussionmentioning
confidence: 95%
“…Summaries of the included papers are provided in Appendix 2 (outcomes) and Appendix 3 (study design). Most studies originated from the USA [20][21][22][23][24][25][28][29][30][31][32][34][35][36][38][39][40][41][42][43][44][45][46][48][49][50][51][52] (88%; n=28), with two studies from Australia 19,33 and single studies from Italy 37 and Japan. 47 The most common study designs were retrospective cohort (44%; n=14), cross-sectional (28%; n=9) and quasi-experimental (14%; n=4).…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%